Evaluation of the sentinel node in breast cancer - preliminary results - Kopacz, Andrzej; Zdzitowiecki, Janusz; Świerblewski, Maciej; Lass, Piotr; Bandurski, Tomasz; Jastrzębski, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2002)
Regional lymph nodes excision is still standard procedure in breast cancer treatment. The aim of this is evaluation of breast cancer metastases occurence in lymph nodes. One of the modern methods of the evaluation of lymph node metastases is the sentinel lymph node dissection. The sentinel lymph node is, from the definition, the first lymph node lying on the road between tumour and the group of the regional lymph nodes. In the theorethical aspects this node is the most suspicious of metastases. In the period 10/1998-04/1999 31 patients with primary operable breast cancer were marked sentinel lymph node. The lymph pathway to axilla was observed in 28 cases and to internal mammary nodes in 2 cases. In one case the pathway was both to the axilla and internal mammary nodes. Sentinel node was estimated by vital blue dye and radioalbeled sulfur colloid method in 16 patients and by vital-blue dye method only in 15 cases. In 10 cases (32%) cancer cells were found in sentinel lymph nodes. In 7 patients sentinel lymph node was the only node with metastases (7/31 - 22.5%). In 8 cases only one sentinel node was detected, in 1 case - two sentinels, and in another one case - three sentinels were detected. In 3 patients sentinel node was estimated as internal mammary node. In one of them metastases were detected and radiotherapy was included as complementary treatment. In 19 cases histopathological examinations confirmed clinical stage (17 cases - N0, 2 cases - N1=pN1). In 7 histopathological examinations it changed stage from N0 to pN1. In these cases sentinel was only metastased node. In another 5 cases clinical stage N1 was changed to pN0. In one patient (P.R.) histological examination did not confirm metastases to axillar lymph node but metastases were present in internal mammary nodes.